Understanding Clinical Significance in Rehabilitation: A Primer for Researchers and Clinicians - Armijo-Olivo, Susan; de Castro-Carletti, Ester Moreira; Calixtre, Letícia Bojikian; de Oliveira-Souza, Ana Izabela Sobral; Mohamad, Norazlin; Fuentes, Jorge (Wolters Kluwer, 2022)
ABSTRACT: The objective of this review was to summarize the concept of clinical significance and associated methods focusing on the area of rehabilitation to provide a resource to rehabilitation researchers and clinicians. Studies were searched on electronic databases from inception until July 28, 2020, with no date or language limits. Manual searches as well as Scopus forward citation for relevant references were performed. Narrative synthesis of study results was performed. Definitions of the concepts related to clinical significance, ways of calculating, and interpreting each method were provided using rehabilitation examples. An explanation of methods to evaluate clinical significance (distribution, anchor, and opinion-based methods) and their advantages and disadvantages were also provided. Considering the limitations of statistical significance in assuring meaningfulness of results, clinical interpretation of research outcomes and the report of clinical significance in intervention trials should be a priority in rehabilitation research. When possible, the use of multiple methods (distribution, anchor, and opinion based) is recommended. Thus, clinical researchers are encouraged to present results in a manner that allow the rehabilitation professionals to easily interpret and implement those results in their clinical practice.